Las depuraciones políticas en la escuela normal nº 2 de Madrid desde el inicio de la guerra civil hasta los albores del régimen franquista - Rosario Morata Sebastián (Universidad Complutense de Madrid, 2006)
In spite of the fact that the incidence of Civil war on Spanish Teaching has been tackled in several works, we believe that its incidence is unknown in the life of "Normal" Schools; this is specially shown in political purges, that obviously have affected students and professors. In this article we explain the implication it has had in nº 2 Normal School of Madrid. It is important to mention that all the used documentation belongs to the Historical File of the Faculty of Education ("María Díaz Jiménez" Building) of the Complutense University of Madrid.